Comparação de duas técnicas educativas: efeitos sobre os fatores de risco de queimaduras em crianças - Milreu, Poliana Galindo de Almeida (2009)
The research has as an objective to verify and compare the changes in the practices that refer to the daily situations of exposures to the risk factors of home burns, considering the mothers of children in the age between 3 and 4 years old using the theater method to the mother s group and the method of expositive dialoged class, to the other mothers group. For the success of this job we use a delineation almost experimental. The dependent variable is represented by the practices which refer to daily situations of exposure to the risk factors of burn in children by home accidents, and the independent variables are the kinds of classes based in different methods. The methodology was divided in three phases: application of a questionnaire after the procedures. The answers were submitted to the analysis and codification according to statistic software and compared by the Wilcoxon and Mann-Whitney tests. In the comparison of the moments of evaluation before and after the procedures, inside each group, we could realize that both had effect, but the first group had a greater evolution than the second. In the comparison between groups we notice that there wasn t an expressive difference that could confirm the hypothesis that the theater method is more efficient than the method of the expositive dialoged class.